2007
DOI: 10.1179/136485907x154548
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary findings from a cross-sectional study on lymphatic filariasis in children, in an area of India endemic forBrugia malayiinfection

Abstract: As the more obvious clinical manifestations of the disease are very uncommon in children, lymphatic filariasis has been considered to be primarily a disease of adults. In many recent reports, however, there is evidence indicating not only that filarial infection is commonly acquired in childhood but also that many infected children already have irreversible damage to their lymphatics. The preliminary results of a cross-sectional study on the patterns of Brugia-attributable pathology in 7934 children (aged 3-15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…This has also been confirmed by prevalence studies on microfilaremia and filarial antigenemia in children [34,35]. Existence of live adult filarial worms has been shown on Doppler sonography and lymphatic dilatation by lymphoscintigraphy in children aged 3-15 yr [13,15]. This lymphatic pathology in infected children, since it is known to persist, might pave way for future development of disease manifestations.…”
Section: Filarial Disease Manifestations In Childrenmentioning
confidence: 58%
See 1 more Smart Citation
“…This has also been confirmed by prevalence studies on microfilaremia and filarial antigenemia in children [34,35]. Existence of live adult filarial worms has been shown on Doppler sonography and lymphatic dilatation by lymphoscintigraphy in children aged 3-15 yr [13,15]. This lymphatic pathology in infected children, since it is known to persist, might pave way for future development of disease manifestations.…”
Section: Filarial Disease Manifestations In Childrenmentioning
confidence: 58%
“…This has been demonstrated in subjects who are clinically asymptomatic except for presence of microfilariae (mf) in blood, by ultrasound examination of the lymphatics of the spermatic cord; lymphoscintigraphy of the limbs and by direct examination of lymph vessels resected by surgery [9,14]. Dilatation of the lymph vessels has been demonstrated by lymphoscintigraphy even in children with brugian filarial infection [15]. It is believed that this damage to lymph vessels is caused by the adult parasites through mediators produced by them, which cause vessel dilatation or inhibit contractility [16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, lymphoscintigraphy studies have shown that asymptomatic infected persons have subclinical disease with considerable structural abnormalities and aberrant lymph flow. [40][41][42] In addition, subclinical lymphatic dysfunction was detectable in LF-infected children despite the absence of clinically evident lymphedema. 43 Therefore, CIC in LF constitutes a complex network modulating the levels of complement fragments, granular proteins, and cytokines/chemokines, which turn profoundly influences disease manifestations in this infection.…”
Section: Discussionmentioning
confidence: 99%
“…This was done by intradermally injecting 0·5 ml of a solution containing 2 μCi of Tc 99m -tagged sulphur colloid into the first web spaces of both feet and hands and the lymphatics were imaged using gamma camera (Shenoy et al 2007b). Dilated lymphatic channels were seen in 80 of the 100 children.…”
Section: Lymphoscintigraphy In Lf Infection In Childrenmentioning
confidence: 99%